2010
DOI: 10.1155/2010/982025
|View full text |Cite
|
Sign up to set email alerts
|

Review of Outcome Information in 46,XX Patients with Congenital Adrenal Hyperplasia Assigned/Reared Male: What Does It Say about Gender Assignment?

Abstract: There is ample historical verification of 46,XX congenital adrenal hyperplasia (CAH) patients being born with essentially male genitaliawhile outcome information is scant. Prior to glucocorticoid therapy, most patients died very young from adrenal insufficiency. Most available reports from laterchildhood, contain little information concerning sexual identity. Reports on older individuals lack adequate information about sexual identity and quality of life. The difficulty in assessing the relative impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
5

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 19 publications
0
33
0
5
Order By: Relevance
“…There are increasing numbers of XY children with ambiguous genitalia being assigned male, and a recent report suggests that male gender assignment is a viable option for XX individuals with congenital adrenal hyperplasia (CAH; Lee & Houk, 2010). Consistent long-term therapeutic follow-ups for these families fulfil a clinical need and offer opportunities for participatory action research (PAR) to improve our knowledge of experiences of families who resist the standard approach of female gender assignment and feminising surgery.…”
Section: Engaging Parents In Dilemmatic Conversationsmentioning
confidence: 99%
“…There are increasing numbers of XY children with ambiguous genitalia being assigned male, and a recent report suggests that male gender assignment is a viable option for XX individuals with congenital adrenal hyperplasia (CAH; Lee & Houk, 2010). Consistent long-term therapeutic follow-ups for these families fulfil a clinical need and offer opportunities for participatory action research (PAR) to improve our knowledge of experiences of families who resist the standard approach of female gender assignment and feminising surgery.…”
Section: Engaging Parents In Dilemmatic Conversationsmentioning
confidence: 99%
“…Among the patients with CAH, complete virilization, such as the male external genitalia with absent testis, is wellknown but actually rare and almost all (~95%) 46, XX CAH infants develop a female phenotype (Lee and Houk 2010). However, the present patient was apparently male and the sexual identity of this particular patient had been male for the last 67 years.…”
Section: Discussionmentioning
confidence: 63%
“…In addition, the patients with 21OHD are associated with marked proliferation of the zonae fasciculate and reticularis especially in untreated conditions with excessive adrenocorticotropic hormone (ACTH) levels, but rarely developed adrenocortical carcinoma, except for a few cases of classical 21OHD (Hamwi et al 1957;Bauman and Bauman 1982;Jaursch-Hancke et al 1988). Virilized 46, XX classical 21OHD patients are rarely raised as male (Lee and Houk 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In defining sexual identity in patients with DSD, one should consider not only the karyotype and anatomical structures but also the social, cultural, intrauterine exposure to androgens and the possibility of fertility [17]. Lee and Houk [18] studied phenotypic male CAH patients with the 46,XX karyotype and concluded that these patients had appropriate levels of social and sexual satisfaction. Our patient presented behaviour consistent with the gender of rearing, with no doubts regarding his sexuality.…”
Section: Discussionmentioning
confidence: 99%